A DESIGN OF PORTABLE MINI SOLAR PANEL COMBINED WITH MICRO HYDROPOWER SYSTEM FOR POWER GENERATION - Awang, Mariah; Mawardi bin Mohd Rani, Muhammad; Diyana binti Abdul Samad, Fadhilah; Syafiq Syazwan, M.M.; Kamaruzaman Musa, Mohd; Rahman, M.A.A; Yusop, Fatimah; Hamidon, Nuramidah (Journal of Sustainable Technology and Applied Science (JSTAS), 2021)
Traditionally, power systems are built to take energy from high-voltage levels and distribute it to lower-voltage networks. Transmission networks are connected to major generating units. However, there will be an excessive number of tiny generators connected to distribution networks in the future. The portable power production system is mostly responsible for the excessive energy delivered, particularly when the user is experiencing a breakdown (function). The loss of integrity, as well as the breakdown and failure of electrical power transmission systems, appears to be an issue rooted (problem statement) in the highly practical and applied domains of electrical and power engineering. The objective of this project is to design and construct a portable power production system that uses renewable energy. The research also aims to determine the maximum and sufficient power consumption from solar energy and micro-hydropower systems in order to provide adequate energy for the space in the event of a power fail. The data for this study was collected using a Digital Multimeter, which was used to measure the resistance (R), voltage (V), current (A), and power (W). The results of the test reveal that the portable power production based on renewable energy has enough capacity to create electricity during a power failure as well as provide adequate loads such as LED lights, mini fans, and phone chargers. This study can also be improved by creating a higher-voltage micro turbine motor and a higher-voltage solar panel for the solar system to increase the operation time.